2010
DOI: 10.1002/jmv.21708
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of group A rotavirus infections in adolescents and adults from Pune, India: 1993–1996 and 2004–2007

Abstract: A total of 1,591 fecal specimens were collected in 1993-1996 and 2004-2007 from adolescents and adults with acute gastroenteritis in Pune, India for detection and characterization of rotavirus. At the two time points, group A rotavirus was detected in 8.6% and 16.2% of the adolescents and 5.2% and 17.2% of the adults, respectively. Reverse transcription-PCR with consensus primers followed by multiplex genotyping PCR detected common strains G1P[8], G2P[4], G3P[8], and G4P[8] in a total of 53.1% of the samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 45 publications
2
20
1
Order By: Relevance
“…But seasonal patterns in tropical climates have shown rates of rotavirus infection throughout the year with seasonal trends that are less well defined (Cook et al, 1990;Levy et al, 2009;Tatte et al, 2010). Also, in the present study a significant difference was observed between virus isolation and cool seasons as the highest prevalence of infection was detected during the coldest months of year, mainly between November and February.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…But seasonal patterns in tropical climates have shown rates of rotavirus infection throughout the year with seasonal trends that are less well defined (Cook et al, 1990;Levy et al, 2009;Tatte et al, 2010). Also, in the present study a significant difference was observed between virus isolation and cool seasons as the highest prevalence of infection was detected during the coldest months of year, mainly between November and February.…”
Section: Discussioncontrasting
confidence: 58%
“…Rotavirus remains a major cause of acute gastroenteritis among infants and children aged <5 years old, not only in the developing countries like Brazil (Sa´fadi et al, 2010), India (Tatte et al, 2010), Cuba (Ribas et al, 2011), but also in developed countries like Italy (Annarita et al, 2010), Swiss (Lacroix et al, 2010) and France (De Rougemont et al, 2011). In recent studies, it was calculated that the rotaviruses cause approximately 111 million episodes of the gastroenteritis requiring only home care, 25 million clinical visits, 2 million hospitalizations and 352,000-592,000 deaths in children aged <5 years old worldwide, each year (Parashar et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was determined that, globally, rotavirus remains a major cause of morbidity and mortality in developing countries [3]. Rotaviruses belong to the family Reoviridae and are classified into 7 antigenic groups (A to G), of which groups A, B, and C are known to infect humans [4]. Group A rotaviruses (RVA) infect all children in their first few years of life and account for the vast majority of rotavirus infections worldwide, while B and C rotaviruses are often found to be associated with outbreaks and sporadic cases [4].…”
Section: Introductionmentioning
confidence: 99%
“…Rotaviruses belong to the family Reoviridae and are classified into 7 antigenic groups (A to G), of which groups A, B, and C are known to infect humans [4]. Group A rotaviruses (RVA) infect all children in their first few years of life and account for the vast majority of rotavirus infections worldwide, while B and C rotaviruses are often found to be associated with outbreaks and sporadic cases [4]. RVA-related diarrhea was ubiquitous; RVA infects almost all children, leading to 9.8 million severe diarrhea episodes and 193,000 child deaths worldwide every year.…”
Section: Introductionmentioning
confidence: 99%